(untitled) (International Journal of Food and Nutritional Sciences, 2022)
IoT has advanced in recent years to become some of the most sophisticated technologies of the twenty-first century. Because of less cost computers, big information, cloud technology, embedded schemes, and intelligent technologies, physical objects can interact and collect information with the least amount of human touch. The major purpose of this article is to show how the Internet of Things may be used to a variety of industries such as healthiness care, agriculture, manufacturing, logistics, and transportation. This research focuses on an e-healthiness information collection, transmission, and monitoring system for cardiac patients, in which a wireless sensor network monitors patients’ healthiness indicators and transmits information to a remote location through GPRS. This research looks at an autonomous irrigation system for intelligent agricultural applications, in which a device screens earth moisture and waters the plant properly, saving time, water, then labour costs.